Aspectos fisiológicos e produtivos de clones de cajueiro anão precoce cultivado sob dois regimes hídricos - Nascimento, Antônio Henrique Cardoso do (2010)
This study aimed to evaluate the physiological and biochemical responses of the clones CCP 76 and BRS 189 of dwarf cashew (Anacardium occidentale L.) that were subjected to two water regimes: irrigated and rainfed conditions. The experiment was conducted in the Experimental Field Curu, Embrapa Tropical in Paraipaba - Ceará, from January to December 2009. Plants of the experiment were in full productive age (5 years). Monthly, we investigated the leaf water content, stomatal conductance to water vapor, transpiration rate, photosynthetic rate, foliar concentrations of inorganic ions and the concentrations of total soluble carbohydrates. In addition, we analyzed the nut productivity and postharvest quality of peduncle. In general, there were no significant differences between plants of the two water regimes for most variables, except foliar concentrations of some ions. This small change was probably due to excess precipitation occurred in the year of the study. Thus, under the conditions studied, the practice of irrigation did not influence the two clones of cashew evaluated. Regarding the two clones: BRS 189 and CCP 76, overall, no significant differences were found, except foliar concentrations of ions K and Ca in the clone CCP 76 when grown under rainfed conditions showed higher content these nutrients in the leaves during the months September to December and staining in the clone CCP 76 showed higher brightness and less red color than plants of the clone BRS 189.